Predator exclusion and riverine input: Effects on sub-Arctic intertidal soft-bottom macrobenthos - Frederike Hoppmann; Bodil A. Bluhm; Rolf Gradinger; Christian Buschbaum; Maeve McGovern; Markus Molis (Journal of Experimental Marine Biology and Ecology, 2026)

Environmental drivers shaping protist plankton seasonality in the northwestern Barents Sea - Lucie Goraguer; Miriam Marquardt; Rolf Gradinger; Doreen Kohlbach; Marit Reigstad; Karen M. Assmann; Melissa Chierici; Anna Maria Dąbrowska; Bente Edvardsen; Elizabeth M. Jones; Håkon Sandven; Zofia Smola; et al. (Progress in Oceanography, 2026)

Extreme mismatch between phytoplankton and grazers during Arctic spring blooms and consequences for the pelagic food-web - Paul E. Renaud; Malin Daase; Eva Leu; Maxime Geoffroy; Sünnje Basedow; Mark Inall; Karley Campbell; Emilia Trudnowska; Einat Sandbank; Frida Cnossen; Muriel Dunn; Lionel Camus; et al. (Progress in Oceanography, 2024)

Sea ice as habitat for microalgae, bacteria, virus, fungi, meio- and macrofauna: A review of an extreme environment - Lars Chresten Lund-Hansen; Rolf Gradinger; Brandon Hassett; Sahan Jayasinghe; Fraser Kennedy; Andrew Martin; Andrew McMinn; Dorte H. Søgaard; Brian K. Sorrell (Polar Biology, 2024)
The novel concept of the review is a focus on the organisms living in the sea ice and what mechanisms they have developed for their existence. The review describes the physical environment of the sea ice and the microorganisms living there as microalgae, bacteria, virus, fungi, meio- and macrofauna where they inhabit the brine channels and exposed to low temperatures as down to −25 °C and high salinities—up to 300. Nutrients, O 2 , CO 2 , pH, light, and UV are also identified as stressors regarding the metabolism of the microorganisms. It is argued that sea ice must be recognized as an extreme environment as based on records of very high or very low concentrations or intensities of the stressors that living organisms in the ice are exposed to and able to endure. Each taxonomic group of organisms in the sea ice are dealt with in detail in terms of the explicit stressors the group is exposed to, and specifically what known mechanisms that the organisms have amended to secure existence and life. These mechanisms are known for some group of organisms as autotrophs, bacteria, meio- and macrofauna but less so for virus and fungi. The review concludes that sea ice is an extreme environment where the stressors vary significantly in both space and time, both in consort and solitary, classifying organisms living there as polyextremophiles and extremophiles. The review relates further to extraterrestrial moons covered with sea ice and these habitats and points toward sea ice on Earth for prospective studies until further technological advances.

Seasonality in phytoplankton communities and production in three Arctic fjords across a climate gradient - Cheshtaa Chitkara; Thomas Juul-Pedersen; Diana Krawczyk; Janne E. Søreide; Anna Vader; Rolf Gradinger; Mie HS Winding; Tobias R Vonnahme (Progress in Oceanography, 2024)

Interannual differences in sea ice regime in the north-western Barents Sea cause major changes in summer pelagic production and export mechanisms - Martí Amargant-Arumí; Oliver Müller; Yasemin V. Bodur; Iliana-V. Ntinou; Tobias Vonnahme; Philipp Assmy; Doreen Kohlbach; Melissa Chierici; Elizabeth Jones; Lasse M. Olsen; Tatiana M. Tsagaraki; Marit Reigstad; et al. (Progress in Oceanography, 2024)

Photophysiological responses of bottom sea-ice algae to fjord dynamics and rapid freshening - Zoé L. Forgereau; Benjamin A. Lange; Rolf Gradinger; Philipp Assmy; Janina E. Osanen; Laura M. García; Janne E. Søreide; Mats A. Granskog; Eva Leu; Karley Campbell (Frontiers in Marine Science, 2023)
Sea ice algae have a broad salinity tolerance but can experience stress during rapid decreases in salinity that occur with seasonal ice melt and during ice sample melt. This study investigated the impact of salinity on the photophysiological responses of bottom-ice algal communities from two Svalbard fjords (Tempelfjorden and Van Mijenfjorden). To further investigate the impact of salinity alone, and particularly to rapid freshening, the responses of a lab-cultured ice algal community from Van Mijenfjorden were assessed. Photophysiological responses were mainly determined via 14 C-based incubations which provided photosynthesis-irradiance curves. Main findings showed that i) the bottom-ice algal community in Tempelfjorden was characterized by lower photosynthetic efficiency and chlorophyll a biomass than the Van Mijenfjorden communities, and ii) a lab-cultured ice algal community from Van Mijenfjorden dominated by pennate diatoms had significantly lower photosynthetic efficiency, maximum photosynthesis and photoacclimation index after a decrease in salinity from 33 to 10. The lower photosynthetic efficiency and chlorophyll a biomass at Tempelfjorden may be attributed to the almost two-fold lower bulk-ice salinity in Tempelfjorden compared to Van Mijenfjorden, which was likely associated with freshwater inputs from the tidewater glacier Tunabreen during sea ice formation. Other factors such as under-ice light intensities, brine volume fraction and brine nutrient concentrations likely also contributed to variability in ice algal response. Furthermore, experimental results indicated that the cultured Van Mijenfjorden community was negatively impacted by a rapid (within 4 to 24 h) reduction in salinity from 33 to 10. We further documented a significant start of recovery of these algae after 168 h. From this work, we surmise that decreases in surface water salinity, for example arising from the intensifying freshening of fjord waters, may only cause temporary changes in ice algal photoacclimation state and thus in chlorophyll a biomass. Further, this study also supports the need for salinity buffered melt of sea ice samples to reduce artificial bias in biological measurements.

Assessing net primary production in the northwestern Barents Sea using in situ, remote sensing and modelling approaches - Laura Castro de la Guardia; Tania Hernández Fariñas; Christian Marchese; Martí Amargant-Arumí; Paul G. Myers; Simon Bélanger; Philipp Assmy; Rolf Gradinger; Pedro Duarte (Progress in Oceanography, 2023)

Seasonal dynamics of sea-ice protist and meiofauna in the northwestern Barents Sea - Miriam Marquardt; Lucie Goraguer; Philipp Assmy; Bodil A. Bluhm; Signe Aaboe; Emily Down; Evan Patrohay; Bente Edvardsen; Agnieszka Tatarek; Zofia Smoła; Jozef Wiktor; Rolf Gradinger (Progress in Oceanography, 2023)

Temporal and spatial variability of sympagic metazoans in a high-Arctic fjord, Svalbard - Vanessa Pitusi; Rolf Gradinger; Janne E. Søreide (Frontiers in Marine Science, 2023)
Svalbard is one of the fastest warming regions in the Arctic including massive loss in fjord sea ice both in terms of area coverage, ice thickness and duration. Sea ice is a habitat for a wide variety of microscopic flora and fauna, and we know little about the impact of accelerated loss of sea ice on this unique sea ice community. Here, we present the first study on the seasonal progression and spatial distribution of the sympagic meiofauna community, in a Svalbard fjord. Further, the meiofauna community in sea ice versus the water column below were compared to investigate the link between the two habitats. In total, we found 12 taxa associated with the sea ice and 15 taxa in the water column below with 11 taxa occurring in both habitats. However, a Canonical-analysis (CA) showed that despite similarities in taxa the two mediums were distinctly different (potentially) due to the low abundance of ice nematodes and polychaete juveniles, in pelagic samples. Temporally, ice meiofauna abundances ranged from 9.7 to 25.3 x 10 3 ind m -2 from beginning of March to end of April, following the seasonal build-up of ice algal biomass from 0.02 to 15.99 mg Chl a m -2 during the same time span. For the transect stations, the lowest ice meiofauna abundance was recorded at the outermost station (VMF2) with 1.6 x 10 3 ind m -2 and the highest abundance at the mid-station MS with 25.3 x 10 3 ind m -2 . Our results indicate that fjord ice harbors most ice algae and sympagic meiofauna in its lower 10-cm with highest values in the lowermost 2-cm, at the sea ice water interface. Sympagic meiofauna communities were mostly dominated by nematodes or polychaete juveniles. We observed the phenology of ice nematodes through the maturation of females and hatching of juveniles from eggs. Polychaete larvae developed (quickly) into juveniles and grew morphological features indicative of readiness for settlement. Thus, we propose, that as with other parts of the Arctic, sea ice in Svalbard fjords plays an important role in the life cycle of ice nematodes and for accelerating the growth of polychaete larvae. Loss of coastal sea ice may therefore negatively impact coastal biodiversity and affect recruitment for some benthic infauna in Svalbard.

What we do in the dark: Prevalence of omnivorous feeding activity in Arctic zooplankton during polar night - Erin H. Kunisch; Martin Graeve; Rolf Gradinger; Hauke Flores; Øystein Varpe; Bodil A. Bluhm (Limnology and Oceanography, 2023)
During the productive polar day, zooplankton and sea‐ice amphipods fulfill a critical role in energy transfer from primary producers to higher trophic‐level species in Arctic marine ecosystems. Recent polar night studies on zooplankton and sea‐ice amphipods suggest higher levels of biological activity than previously assumed. However, it is unknown if these invertebrates maintain polar night activity on stored lipids, opportunistic feeding, or a combination of both. To assess how zooplankton (copepods, amphipods, and krill) and sea‐ice amphipods support themselves on seasonally varying resources, we studied their lipid classes, fatty acid compositions, and compound‐specific stable isotopes of trophic biomarker fatty acids during polar day (June/July) and polar night (January). Lipid storage and fatty acid results confirm previously described dietary sources in all species during polar day. We found evidence of polar night feeding in all species, including shifts from herbivory to omnivory. Sympagic‐, pelagic‐, and Calanus spp.‐derived carbon sources supported zooplankton and sea‐ice amphipods in both seasons. We provide a first indication of polar night feeding of sea‐ice amphipods in the pelagic realm.

Earlier sea-ice melt extends the oligotrophic summer period in the Barents Sea with low algal biomass and associated low vertical flux - Doreen Kohlbach; Lucie Goraguer; Yasemin V. Bodur; Oliver Müller; Martí Amargant-Arumí; Katalin Blix; Gunnar Bratbak; Melissa Chierici; Anna Maria Dąbrowska; Ulrike Dietrich; Bente Edvardsen; Laura M. García; et al. (Progress in Oceanography, 2023)

First trait-based characterization of Arctic ice meiofauna taxa - Evan Patrohay; Rolf Gradinger; Miriam Marquardt; Bodil A. Bluhm (Polar Biology, 2022)
Trait-based approaches connect the traits of species to ecosystem functions to estimate the functional diversity of communities and how they may respond to environmental change. For the first time, we compiled a traits matrix across 11 traits for 28 species of Arctic ice meiofauna, including Copepoda (Subclass), Nematoda (Phylum), Acoela (Order), Rotifera (Phylum), and Cnidaria (Phylum). Over 50 years of pan-Arctic literature were manually reviewed, and trait categories were assigned to enable future trait–function connections within the threatened ice-associated ecosystem. Approximately two-thirds of the traits data were found at the genus or species level, ranging from 44% for Nematoda to 100% for Cnidaria. Ice meiofauna were shown to possess advantageous adaptations to the brine channel network within sea ice, including a majority with small body widths < 200 μm, high body flexibility, and high temperature and salinity tolerance. Diets were found to be diverse outside of the algal bloom season, with most organisms transitioning to ciliate-, omnivore-, or detritus-based diets. Eight species of the studied taxa have only been recorded within sea ice, while the rest are found in a mixture of sympagic–pelagic–benthic habitats. Twelve of the ice meiofauna species have been found with all life stages present in sea ice. Body width, temperature tolerance, and salinity tolerance were identified as traits with the largest research gaps and suffered from low-resolution taxonomic data. Overall, the compiled data show the degree to which ice meiofauna are adapted to spending all or portions of their lives within the ice.

Connections to the Deep: Deep Vertical Migrations, an Important Part of the Life Cycle of Apherusa glacialis, an Arctic Ice-Associated Amphipod - Magnus Drivdal; Erin H. Kunisch; Bodil A. Bluhm; Rolf Gradinger; Stig Falk-Petersen; Jørgen Berge (Frontiers in Marine Science, 2021)
Arctic sea ice contains a substantial amount of living biota of which part is lost through melt and export out of the Arctic Ocean every year. It is unclear how populations can be maintained within the Arctic Ocean. A representative ice inhabitant, the amphipod Apherusa glacialis was previously assumed to spend its entire life in the sea ice habitat, hence being dependent on sea ice to complete its life cycle. However, several recent studies report pelagic occurrences and suggest that seasonal vertical migrations might be an adaptive life history trait enabling a viable population size in the Arctic Ocean. In this study we use a particle-tracking model to investigate to what extent vertical migration might affect the species’ retention in the Arctic Ocean and the sea ice habitat. The modeled trajectories of A. glacialis were calculated based on ice drift and ocean currents from a coupled ocean – sea ice model covering the Arctic Ocean. We test two scenarios: (1) trajectories of A. glacialis that stay attached to the ice or follow the surface currents if they melt out of the ice and (2) trajectories of A. glacialis that undertake a seasonal vertical migration to drift with the currents at depth for parts of the year. In the multi-year model simulations it is assumed that after an initial period of 2 years A. glacialis that are located outside sea-ice cover each spring will perish while those located within the ice-covered region will reproduce. The model results show that a seasonal vertical migration both increases the total number of individuals and leads to a population distribution within the Arctic Ocean more in line with previous findings than the results from the non-migrating A. glacialis . Our results support the hypothesis that a seasonal migration may be an adaptive life history strategy in this species.

Ice-Associated Amphipods in a Pan-Arctic Scenario of Declining Sea Ice - Haakon Hop; Mikko Vihtakari; Bodil A. Bluhm; Malin Daase; Rolf Gradinger; Igor A. Melnikov (Frontiers in Marine Science, 2021)
Sea-ice macrofauna includes ice amphipods and benthic amphipods, as well as mysids. Amphipods are important components of the sympagic food web, which is fuelled by the production of ice algae. Data on the diversity of sea-ice biota have been collected as a part of scientific expeditions over decades, and here we present a pan-Arctic analysis of data on ice-associated amphipods and mysids assimilated over 35 years (1977–2012). The composition of species differed among the 13 locations around the Arctic, with main differences between basins and shelves and also between communities in drift ice and landfast sea ice. The sea ice has been dramatically reduced in extent and thickness during the recorded period, which has resulted in reduced abundance of ice amphipods as well as benthic amphipods in sea ice from the 1980’s to the 2010’s. The decline mainly involved Gammarus wilkitzkii coinciding with the disappearance of much of the multiyear sea ice, which is an important habitat for this long-lived species. Benthic amphipods were most diverse, and also showed a decline over the time-span. They had higher abundance closer to land where they are associated with landfast ice. However, they also occurred in the Central Arctic Ocean, which is likely related to the origin of sea ice over shallow water and subsequent transport in the transpolar ice drift. Recent sampling in the waters east and north of Svalbard has found continued presence of Apherusa glacialis , but almost no G. wilkitzkii . Monitoring by standardized methods is needed to detect further changes in community composition of ice amphipods related to reductions in sea-ice cover and ice type.

Seasonal Variability in the Zooplankton Community Structure in a Sub-Arctic Fjord as Revealed by Morphological and Molecular Approaches - Estelle Coguiec; Elizaveta A. Ershova; Malin Daase; Tobias R. Vonnahme; Owen S. Wangensteen; Rolf Gradinger; Kim Præbel; Jørgen Berge (Frontiers in Marine Science, 2021)
Phyto- and zooplankton in Arctic and sub-Arctic seas show very strong seasonal changes in diversity and biomass. Here we document the seasonal variability in the mesozooplankton community structure in a sub-Arctic fjord in Northern Norway based on monthly sampling between November 2018 and February 2020. We combined traditional morphological zooplankton identification with DNA metabarcoding of a 313 base pair fragment of the COI gene. This approach allowed us to provide the most detailed mesozooplankton species list known for this region across an entire year, including both holo- and meroplankton. The zooplankton community was dominated by small copepods throughout the sampling period both in terms of abundance and relative sequence counts. However, meroplankton was the most diverse group, especially within the phylum polychaeta. We identified four distinct periods based on the seasonal analysis of the zooplankton community composition. The pre-spring bloom period (February–March) was characterized by low abundance and biomass of zooplankton. The spring bloom (April) was characterized by the presence of Calanus young stages, cirripedia and krill eggs. The spring-summer period (May–August) was characterized by a succession of meroplankton and a relatively high abundance of copepods of the genus Calanus spp. Finally, the autumn-winter period (September–December) was characterized by a high copepod diversity and a peak in abundance of small copepods (e.g., Oithona similis , Acartia longiremis , Pseudocalanus acuspes , Pseudocalanus elongatus , Pseudocalanus moultoni , Pseudocalanus minutus ). During this period, we also observed an influx of boreal warm-water species which were notably absent during the rest of the year. Both the traditional community analysis and metabarcoding were highly complementary and with a few exceptions showed similar trends in the seasonal changes of the zooplankton community structure.

Crude oil exposure reduces ice algal growth in a sea-ice mesocosm experiment - Kyle Dilliplaine; Marc Oggier; R. Eric Collins; Hajo Eicken; Rolf Gradinger; Bodil A. Bluhm (Polar Biology, 2021)

Changes in Sea-Ice Protist Diversity With Declining Sea Ice in the Arctic Ocean From the 1980s to 2010s - Haakon Hop; Mikko Vihtakari; Bodil A. Bluhm; Philipp Assmy; Michel Poulin; Rolf Gradinger; Ilka Peeken; Cecilie von Quillfeldt; Lasse Mork Olsen; Ludmila Zhitina; Igor A. Melnikov (Frontiers in Marine Science, 2020)

What Feeds the Benthos in the Arctic Basins? Assembling a Carbon Budget for the Deep Arctic Ocean - Ingrid Wiedmann; Elizaveta Ershova; Bodil Annikki Bluhm; Eva-Maria Nöthig; Rolf R. Gradinger; Ksenia Kosobokova; Antje Boetius (Frontiers in Marine Science, 2020)

Spatial distribution of aquatic marine fungi across the western Arctic and sub‐arctic - Brandon T. Hassett; Anne‐Lise L Ducluzeau; Roy E. Collins; Rolf Gradinger (Environmental Microbiology, 2017)
Summary Fungi are important parasites of primary producers and nutrient cyclers in aquatic ecosystems. In the Pacific‐Arctic domain, fungal parasitism is linked to light intensities and algal stress that can elevate disease incidence on algae and reduce diatom concentrations. Fungi are vastly understudied in the marine realm and knowledge of their function is constrained by the current understanding of fungal distribution and drivers on global scales. To investigate the spatial distribution of fungi in the western Arctic and sub‐Arctic, we used high throughput methods to sequence 18S rRNA, cloned and sequenced 28S rRNA and microscopically counted chytrid‐infected diatoms. We identified a broad distribution of fungal taxa predominated by Chytridiomycota and Dikarya. Phylogenetic analysis of our Chytridiomycota clones placed Arctic marine fungi sister to the order Lobulomycetales. This clade of fungi predominated in fungal communities under ice with low snowpack. Microscopic examination of fixed seawater and sea ice samples revealed chytrids parasitizing diatoms collected across the Arctic that notably infected 25% of a single diatom species in the Bering Sea. The Pezizomycotina comprised > 95% of eukaryotic sequence reads in Greenland, providing preliminary evidence for osmotrophs being a substitute for algae as the base of food webs.

The diversity, abundance and fate of ice algae and phytoplankton in the Bering Sea - Anna Szymanski; Rolf Gradinger (Polar Biology, 2016)

Fatty acid and stable isotope characteristics of sea ice and pelagic particulate organic matter in the Bering Sea: tools for estimating sea ice algal contribution to Arctic food web production - Shiway W. Wang; Suzanne M. Budge; Rolf R. Gradinger; Katrin Iken; Matthew J. Wooller (Oecologia, 2014)

Growth rates of arctic juvenile Scolelepis squamata (Polychaeta: Spionidae) isolated from Chukchi Sea fast ice - Brenna McConnell; Rolf Gradinger; Katrin Iken; Bodil A. Bluhm (Polar Biology, 2012)

Holes in Progressively Thinning Arctic Sea Ice Lead to New Ice Algae Habitat - Sang Heon Lee; C. Peter McRoy; Hyoung Min Joo; Rolf Gradinger; Huehua Cui; Mi Sun Yun; Kyung Ho Chung; Sung-Ho Kang; Chang-Keun Kang; Eun Jung Choy; SeungHyun Son; Eddy Carmack; et al. (Oceanography, 2011)

Arctic Marine Biodiversity: An Update of Species Richness and Examples of Biodiversity Change - Bodil Bluhm; Andrey Gebruk; Rolf Gradinger; Russell Hopcroft; Falk Huettmann; Ksenia Kosobokova; Boris Sirenko; Marcin Weslawski (Oceanography, 2011)

Editorial - Arctic Ocean Diversity: synthesis - Bodil A. Bluhm; Rolf Gradinger; Russell R. Hopcroft (Marine Biodiversity, 2011)

The pan-Arctic biodiversity of marine pelagic and sea-ice unicellular eukaryotes: a first-attempt assessment - Michel Poulin; Niels Daugbjerg; Rolf Gradinger; Ludmila Ilyash; Tatiana Ratkova; Cecilie von Quillfeldt (Marine Biodiversity, 2011)

Small scale vertical gradients of Arctic ice algal photophysiological properties - Sarah Story Manes; Rolf Gradinger (Photosynthesis Research, 2009)

Using stable isotopes to assess carbon and nitrogen turnover in the Arctic sympagic amphipod Onisimus litoralis - Mette R. Kaufman; Rolf R. Gradinger; Bodil A. Bluhm; Diane M. O’Brien (Oecologia, 2008)

First record of sympagic hydroids (Hydrozoa, Cnidaria) in Arctic coastal fast ice - Bodil A. Bluhm; Rolf Gradinger; Stefano Piraino (Polar Biology, 2007)

Arctic Ocean Exploration 2002 - Rolf Gradinger; Bodil Bluhm (Polar Biology, 2005)

Abundance and composition of the sea-ice meiofauna in off-shore pack ice of the Beaufort Gyre in summer 2002 and 2003 - Rolf R. Gradinger; Klaus Meiners; Gerry Plumley; Qing Zhang; Bodil A. Bluhm (Polar Biology, 2005)

Editorial - Gotthilf Hempel; Irmtraut Hempel; Rolf Gradinger (Polar Biology, 2004)

Meiofauna in sea ice of the Weddell Sea (Antarctica) - Sigrid Schnack-Schiel; David Thomas; Rolf Gradinger; Melnikov I.; Michael Spindler; Gerhard Dieckmann (Polar Biology, 2001)

Turbellaria (Archoophora: Acoela) from Antarctic sea ice endofauna - examination of their micromorphology - Hans Heinrich Janssen; Rolf Gradinger (Polar Biology, 1999)

Flagellates and heliozoans in the Greenland Sea ice studied alive using light microscopy - J. Ikävalko; Rolf Gradinger (Polar Biology, 1997)

Vertical distribution of bacteria in Arctic sea ice from the Barents and Laptev Seas - Rolf Gradinger; Qing Zhang (Polar Biology, 1997)